Analysis Relationship of Imported Rice with Rice Production, Imported and Domestic Rice Prices with VECM - Abyan Rai; Sasmito Hadi Wibowo (Jurnal Matematika, Statistika dan Komputasi, 2020)
Rice is the main food for most Indonesians. With much natural resources, Indonesia can naturally fulfill its own rice consumption needs. However, Indonesia actually relies on imports to meet consumption needs. Even Indonesia continues to import while rice production is volatility surplus to maintain domestic rice prices. Based on these problems, this study aims to analyze the relationship of volume of imported rice with rice production, domestic rice prices, and prices of imported rice. The method used is descriptive analysis and Vector Error Correction Model (VECM). In the long-term, rice production and domestic rice prices have significant effect on Indonesia's rice import volume. In short-term, rice production and domestic rice prices have significant effect on Indonesian rice import volume. The results of the causality test show that there is a two-way relationship between Indonesian rice import volume and Indonesian production rice. Meanwhile, a one-way relationship occurs when imported rice volumes influenced by prices of domestic rice.